Traffic Education In Contemporary Islamic Education Curriculum In Indonesia - Yahiji, Kasim; Sukmawati, Heni; Alfin, Jauharoti; Mahfud, Choirul (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2018)
Abstract Islamic studies that discuss the issue of traffic education in contemporary Islamic education curriculum in Indonesia are necessary to be followed up more seriously. In this context, the main purpose of this research is to find out what and how the problems of traffic as well as traffic education in Indonesia? What is the urgency of developing a traffic education curriculum in an Islamic perspective? This paper is written using qualitative data which is based on references and literature on books, news, journals and opinions in the mass media and other relevant sources in the study of the development of the traffic education in contemporary Islamic education curriculum in Indonesia. The results of the study show that: First, the problem of traffic education in Indonesia is very complex. From day to day, we know that the number of accidents has not yet dropped significantly.Even the highest accident rates occur in the age of students and school children. Secondly, the development of a traffic education curriculum in an Islamic perspective is very urgent given the many problems caused by the many factors underlying traffic accidents. Muslims and Islamic education institutions in this country should take a role of the awareness of students and schoolchildren to carefully keep trying to realize, know and obey all traffic rules for the safety and common good. Keywords: Traffic Problems, Curriculum Development and Islamic Education